Pertimbangan Hakim Terkait Penolakan Permohonan Poligami - Mustika Anggraeni Dwi Kurnia; Ahdiana Yuni Lestari (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2022)
In order to obtain a permit for a polygamous marriage that is legal in the eyes of the state, a husband must apply for polygamy to the Religious Courts in his area and must meet the requirements set forth in the Marriage Law Articles 4 and 5. However, in practice, polygamous marriages are preceded by sirri marriages first. The purpose of this study is to present the basis for the judge's considerations in rejecting the decision on the licensing of polygamy which was preceded by sirri marriage at the Bantul Religious Court and the legal consequences that occurred to the second wife, joint assets, and children born as a result of refusing permission to polygamy. This type of research is normative research with data collection techniques using literature and interviews with informants. The source person was Dra H. Nafilah S.H M.H. The judge who decided this case at the Bantul Religious Court. The analysis technique uses qualitative data with descriptive methods. Based on the results of the study, it can be concluded that the Judge's considerations in rejecting the application for a polygamy permit are in accordance with Articles 4 and 5 of the Marriage Law, Al-Quran Surah An-Nisa verse 3, and the Book of Fiqh, which in essence the Petitioner does not meet the alternative and cumulative requirements if do itsbat marriage, the application will still be rejected in accordance with the provisions of SEMA Number 03 of 2018. The legal consequences of refusing the permit for polygamy for the second wife are that they do not receive an inheritance if their husband dies and they do not receive joint assets if they divorce